Pola Komunikasi Rentas Sempadan di Telok Melano-Temajuk, Borneo Barat : Satu Analisis Teori Akomodasi Komunikasi = Patterns of Cross-Border Communication in Telok Melano-Temajuk, West Borneo : An Analysis of Communication Accommodation Theory - Dilah, Tuah; Chong, Shin (Penerbit UKM (UKM Press), 2024)
The Telok Melano, Sarawak (Malaysia), and Temajuk, West Kalimantan (Indonesia) border communities existed in the early 1980’s has created a unique communication pattern in West Borneo. In the early stages, both speakers in Telok Melano-Temajuk had spoken a similar language variation called Malay Sambas dialect. After four decades of the border community formation (1980-2020), the communication pattern in both areas has experienced a significant change. Thus, the objective of this study is to analyse the cross-border communication pattern of Telok Melano-Temajuk based on Gilles’ Communication Accommodation Theory. Research data were obtained using qualitative approach through recordings, interviews, and participant observations. There are five dialogue samples obtained from the speakers from Telok Melano-Temajuk for analysis. Every interaction in the dialogue was analysed using convergence and divergence strategy to identify the border community communication pattern in West Borneo. The study found the border community communication pattern in West Borneo had contributed to the integration phenomenon and language variation choice in daily interaction of two community groups living in proximity but separated by international border. From the communication accommodation perspective, the communication pattern at Telok Melano-Temajuk is different according to the informant’s age. The older generation at Telok Melano was found to use the convergence strategy when interacting with speakers from Temajuk by switching from Telok Melano Malay dialect to Desa Temajuk Malay dialect. On the other hand, the younger generation at Telok Melano was found to begin its transition to the Sarawak Malay dialect, specifically the Kuching variation which is Sarawak’s lingua franca. The finding in this study is important to record the border community’s communication pattern transition after the opening of the Telok Melano-Sematan alignment of the Pan-Borneo Highway.